Perception, Experience and Care of Episiotomy among Post Natal Women Attending Selected Health Facilities in Ibadan, Nigeria (2019)
Background: Episiotomy is a deliberate cut given on the perineum to widen the vaginal opening for the delivery of an infant but it is sometimes misused. The study aimed at determining the perception, experience and care of episiotomy among postnatal women. Methods: This descriptive study was carried out in one selected tertiary, secondary and primary health care facility respectively in Ibadan. Purposive sampling techniques was used to select 219 participants. Data was collected using a self-structured questionnaire with reliability of 0.81 after obtaining ethical approval and informed consent. Two hundred (200) questionnaires were suitable for data analysis. Data were analysed using descriptive statistics and hypotheses were tested using chi-square at p<0.05. Results: One hundred and seventeen (58.5%) of the respondents were between ages 28-37 years with a mean age of 29.7 years. A total of 108(54.0%) of the respondents had experienced episiotomy. Informed consents were not obtained from most of the respondents before episiotomies were performed on them. Also, 78(72.2%) affirmed that they experienced pain and discomfort from episiotomy with 31 (28.7%) admitting that the pain affected their ability to care for their babies while 16 (14.8%) affirmed that the experience also resulted in discomfort during sexual intercourse. Furthermore, 92(85.2%) out of the 108 claimed that they were given information on the care of episiotomy after the procedure and thus, were able to use the various methods of episiotomy care effectively without any complications. Conclusion: Episiotomy rate in this study was higher than the recommended evidenced-based rate for optimum care. Therefore, efforts should be made to- reduce the rate at which episiotomies are performed by health workers on parturient mothers. In addition, women should be given appropriate information on episiotomy.